Proof of the Accuracy of Calculation of Trigonometric Formulas for Spherical Triangles with Magnetic Declination Correction at Istiwa A'zam in Determining the Direction of the Qibla - Caniago, Abdi Samra; Athar, Gadis Arniyati (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This study departs from Arbisora's research which shows that there is a difference in the direction of the Qibla of the Al-Mashun Grand Mosque in Medan which is determined by the hisab method and the rashdul Qibla method. The researcher's temporary assumption is that this is because the hisab does not use magnetic declination. This study aims to prove the accuracy of the Qibla direction using the spherical triangle trigonometric hisab method with magnetic declination correction and the istiwa a'zam event. The research is field research, which was carried out at the Al-Mashun Grand Mosque in Medan City on July 15, 2024 which coincided with the istiwa a'zam event. The coordinate data of the Al-Mashun Grand Mosque in Medan was obtained from Garmin GPS 60, which is 98°41' 4.14